Scaling climate-smart innovations in Senegal - Ewell, Hanna Louise Deborah; Carbonell Barlis, Angelica; Worou, Nadine; Diedhiou, Lamine (2025)
Since 2021, over 1.2 million farmers and value chain actors have accessed climate-smart agriculture (CSA) technologies and climate information services (CIS), proving the potential of bundled innovations to build resilience. This achievement demonstrates the viability of scaling climate-smart innovations through institutional partnerships and bundled approaches that combine improved seeds, soil management, livestock practices, and climate forecasts. Scaling efforts in Senegal emphasize responsible, gender-responsive, and participatory pathways, with communities, women, and youth engaged through tailored services, finance, and hybrid communication systems.